Glyphosate-Resistant Parthenium hysterophorus in the Caribbean Islands: Non Target Site Resistance and Target Site Resistance in Relation to Resistance Levels - Bracamonte, Enzo; Fernández-Moreno, Pablo T.; Barro, Francisco; De Prado, Rafael (Frontiers in Plant Science, 2016)
Glyphosate has been the most intensely herbicide used worldwide for decades, and continues to be a single tool for controlling weeds in woody crops. However, the adoption of this herbicide in a wide range of culture systems has led to the emergence of resistant weeds. Glyphosate has been widely used primarily on citrus in the Caribbean area, but a study of resistance in the Caribbean islands of Cuba and the Dominican Republic has never been carried out. Unfortunately, Parthenium hysterophorus has developed glyphosate-resistance in both islands, independently. The resistance level and mechanisms of different P. hysterophorus accessions (three collected in Cuba (Cu-R) and four collected in the Dominican Republic (Do-R) have been studied under greenhouse and laboratory conditions. In in vivo assays (glyphosate dose causing 50% reduction in above-ground vegetative biomass and survival), the resistance factor levels showed susceptible accessions (Cu-S≥Do-S), low-resistance accessions (Cu-R3<Do-R4), medium-resistance accessions (Do-R3< Cu-R2 < Do-R2) and high-resistance accessions (Do-R1<Cu-R1). In addition, the resistance factor levels were similar to those found in the shikimic acid accumulation at 1000 μM of glyphosate (Cu-R1≥Do-R1>Do-R2>Cu-R2>Do-R3>Do-R4>Cu-R3>>Cu-S≥Do-S). Glyphosate was degraded to aminomethylphosphonic acid, glyoxylate and sarcosine by >88% in resistant accessions except in Cu-R3 and Do-R4 resistant accessions (51.12 and 44.21, respectively), whereas a little glyphosate (<9.32%) was degraded in both susceptible accessions at 96 h after treatment. There were significant differences between P. hysterophorus accessions in the 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) activity enzyme with and without different glyphosate rates. The R accessions showed values of between 0.026 and 0.21 µmol µg-1 TSP protein min-1 basal EPSPS activity values with respect to the S (0.024 and 0.025) accessions. The same trend was found in the EPSPS enzyme activity treated with glyphosate, where a higher enzyme activity inhibition (glyphosate µM) corresponded to greater resistance levels in P. hysterophorus accessions. One amino acid substitution was found at position 106 in EPSPS, consisting of a proline to serine change in Cu-R1, Do-R1 Do-R2. The above-mentioned results indicate that high resistance values are determined by the number of defense mechanisms (target-site and non-target-site resistance) possessed by the different P. hysterophorus accessions, concurrently.